Restriksi Perempuan untuk Berpolitik Melalui Drama (Studi Kasus Drama Korea Rookie Historian Goo Hae Ryung) - Theonaldy, Kriston; Azeharie, Suzy (Koneksi, 2023)
New media is one part of mass media. Netflix is ​​a streaming viewing application and is part of new media. Hallyu wave is Korean culture which is currently popular in many countries. Korean dramas are part of the hallyu wave. On July 17, 2019, Netflix released a Korean drama entitled Rookie Historian Goo Hae Ryung. This drama tells about the struggles of female historians in the Joseon era who experienced restrictions on politics. Historians are part of the Chunchugwan Office in charge of recording activities within the kingdom. This study discusses the forms of restrictions on women's participation in politics during the Joseon dynasty. In this research, the writer uses the silent group theory from Cheris Kramarae. This study uses a qualitative approach with Sara Mills critical discourse analysis Method. The data in this study were obtained through interviews, observations, literature studies, and documentation. The results showed that there were five forms of restrictions on women's participation in politics during the Joseon dynasty era in the Korean drama Rookie Historian Goo Hae Ryung, namely the prohibition of the right to freedom, recognition, exclusion, violence, and verbal abuse. Media baru adalah salah satu bagian media massa. Netflix merupakan aplikasi menonton streaming dan merupakan bagian dari media baru. Hallyu wave adalah budaya Korea yang sedang populer di banyak negara. Drama Korea merupakan bagian dari hallyu wave. Pada 17 Juli 2019, Netflix merilis drama Korea berjudul Rookie Historian Goo Hae Ryung. Drama ini menceritakan tentang perjuangan perempuan sejarawan pada era Joseon yang mengalami pembatasan berpolitik. Sejarawan merupakan bagian dari Kantor Chunchugwan yang bertugas untuk mencatat kegiatan dalam kerajaan. Penelitian ini membahas tentang bentuk pembatasan perempuan untuk berpolitik pada era dinasti Joseon. Dalam penelitian ini, penulis menggunakan teori kelompok terbungkam dari Cheris Kramarae. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis wacana kritis Sara Mills. Data dalam penelitian ini didapatkan melalui hasil wawancara, observasi, studi pustaka, dan dokumentasi. Hasil penelitian menunjukan ada lima bentuk pembatasan perempuan untuk berpolitik pada era dinasti Joseon dalam drama Korea Rookie Historian Goo Hae Ryung, yaitu pelarangan hak kebebasan, pengakuan, pengecualian, kekerasan, dan pelecehan verbal.